Acceptability and feasibility of tuberculosis-diabetes mellitus screening implementation in private primary care clinics in Yogyakarta, Indonesia: a qualitative study - Denny Anggoro Prakoso; Wahyudi Istiono; Yodi Mahendradhata; Merita Arini (BMC, 2023)
Abstract Background The relationship between Tuberculosis (TB) and Diabetes Mellitus (DM) is intricate and intertwined, posing significant global health challenges. In addition, the increasing prevalence of DM worldwide raises concerns regarding the potential resurgence of tuberculosis. The implementation of tuberculosis prevention strategies is of the utmost importance, especially in countries like Indonesia that encounter a dual burden of TB and DM. The significance of TB screening in private primary care settings for patients with diabetes cannot be overstated. Implementing TB screening protocols in private primary care settings can assist in identifying diabetic patients with tuberculosis. Therefore, this study aims to explore the acceptability and feasibility of tuberculosis-diabetes mellitus screening implementation in private primary care clinics. Methods We conducted implementation research with an exploratory qualitative design. Fifteen healthcare professionals from five private primary health care clinics in Yogyakarta, Indonesia, participated in five focus groups. The discussions were audio recorded, transcribed verbatim, and thematically analyzed. As part of the feasibility assessment, surveys were conducted in each clinic. We conducted a thematic analysis in accordance with the theoretical framework of acceptability and the feasibility assessment. Results We identified that most private primary care clinics deemed the implementation of TB screening in DM patients acceptable and practicable. We revealed that the majority of diabetes patients enthusiastically accepted TB-DM screening services. In addition, we found that the healthcare professionals at the clinic are aware of the nature of the intervention and demonstrates a positive attitude despite a subtle burden. The stigma associated with COVID-19 has emerged as a new implementation barrier, joining TB stigma, lack of resources, and regulatory issues. We identify concealed and tiered screening as a potential method for enhancing the implementation of TB-DM screening. Conclusions The implementation of TB screening in DM patients in private primary care clinics had the potential to be acceptable and feasible. To achieve a successful implementation, consideration should be given to supporting factors, hindering factors, and strategies to improve TB screening in DM patients.